PENGEMBANGAN PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS SAINTIFIK PADA PEMBELAJARAN IPA KELAS VI SDN GANDASARI 1 - Sri Rahayu Kurniasih (Universitas Islam Syekh Yusuf, 2021)
The purpose of this research is to develop teaching materials in the form of Scientific-based LKPD in science learning and knowing the quality of the material teaching in the form of LKPD produced. This study uses the Borg model and Gall. The population in this study was class VI at SDN Gandasari 1. The sampling technique in this study used a small-scale questionnaire and large scale. Small-scale sampling of 10 people from class VI and dam large-scale sampling of 23 people from class VI. Instruments that used include interviews, questionnaires, and test instruments. Research result this development meets the